Using evidence to influence policy: Oxfam's experience. Issue 1 (December 2018) - Mayne, Ruth; Green, Duncan; Guijt, Irene; Walsh, Martin; English, Richard; Cairney, Paul
Abstract Policymaking is rarely 'evidence-based'. Rather, policy can only be stronglyevidence-informed if its advocates act effectively. Policy theories suggest that they can do so by learning the rules of political systems, and by forming relationships and networks with key actors to build up enough knowledge of their environment and trust from their audience. This knowledge allows them to craft effective influencing strategies, such as to tell a persuasive and timely story about an urgent policy problem and its most feasible solution. Empirical case studies help explain when, how, and why such strategies work in context. If analysed carefully, they can provide transferable lessons for researchers and advocates that are seeking to inform or influence policymaking. Oxfam Great Britain has become an experienced and effective advocate of evidence-informed policy change, offering lessons for building effective action. In this article, we combine insights from policy studies with specific case studies of Oxfam campaigns to describe four ways to promote the uptake of research evidence in policy: (1) learn how policymaking works, (2) design evidence to maximise its influence on specific audiences, (3) design and use additional influencing strategies such as insider persuasion or outsider pressure, and adapt the presentation of evidence and influencing strategies to the changing context, and (4) embrace trial and error. The supply of evidence is one important but insufficient part of this story.